A case of advanced oral undifferentiated carcinoma successfully treated by concomitant chemoradiotherapy - Shindo, Junichi; Kamata, Hitoshi; Akasaka, Yoko; Watanabe, Yoshihisa; Jinbu, Yoshinori; Takagi, Shinobu (Journal of Japanese Society of Oral Oncology, 1995)
We experienced an advanced case of oral undifferentiated carcinoma which was widely spread from lower lip to the entire region of lower gingiva and floor of mouth. The patient was a 50-year-old male who complained of gingival retraction and pain at lower frontal teeth. There were no abnormal findings in panoramic tomograph and CT, however, Tc-99m MDP accumulation was observed at the mandible in bone scintigraphy and Ga-67 accumulation at the region of both side of cervical lymph nodes in Ga-67 scintigraphy. Histopathological examination showed an undifferentiated carcinoma. The patient was successfully treated by concomitant chemo-radiotherapy (PEP : 120mg, 60Co : 49.9 Gy), and the shape and function of the mouth was completely preserved. There have been no recurrences at least 1 year and 6 months after treatment.